A Short Review on Drag-Reduced Turbulent Flow of Inhomogeneous Polymer Solutions. (16th December 2013) - Fu, Zaiguo; Kawaguchi, Yasuo
Abstract : Turbulent drag reduction by additives is an effective approach to save energy in wall turbulence. Improvement of this approach requires a better understanding of the interactions between turbulence and additives including the complex changes in turbulence under various conditions of additives. In this paper we review some recent progress in the investigations of drag reduction in wall turbulence with inhomogeneous polymer solutions via slot-injection and wall-blowing methods. The turbulent statistics characteristics and coherent structures modified by the inhomogeneous polymer additives and the polymer diffusion characteristics in the turbulent boundary layer (TBL) flow and channel flow are discussed in terms of previous experimental and numerical studies. This review also presents a discussion of current limitations and future directions in these areas. Readers may find it helpful in understanding the phenomenon of turbulent drag reduction by inhomogeneous polymer additives and in developing practical applications.